THE EFFECT OF MILKFISH (Chanos chanos) BONE FLOUR FORTIFICATION ON THE PHYSICOCHEMICAL CHARACTERISTICS AND ACCEPTABILITY OF WHITE BREAD - Mahfiroh, Ririn; Sahidu, Adriana Monica; Pujiastuti, Dwi Yuli (Jurnal Perikanan Unram, 2025)
Milkfish bone waste is a by product of the fisheries industry that has not been fully utilized, despite its high calcium and protein content, making it a potential ingredient for food fortification. Meanwhile, white bread, a widely consumed food in the community, is known to have low calcium content. This study aims to evaluate the effect of adding milkfish bone flour on the physicochemical characteristics and consumer acceptability of white bread. The research was conducted using a Completely Randomized Design (CRD) with five levels of fortification concentration: 0%, 2.5%, 5%, 7.5%, and 10%, each with four replications. The parameters analyzed included moisture, protein, ash, and calcium content, as well as texture attributes such as hardness, cohesiveness, springiness, and chewiness, along with hedonic tests for color, taste, texture, and aroma. The results showed that fortification with milkfish bone flour had a significant effect (p<0.05) on most parameters, except for color. Increasing the fortification concentration resulted in higher protein, ash, and calcium levels, while moisture content and certain texture parameters decreased. The best treatment was found at 5% fortification (P2), based on Bayes analysis, with the highest scores across all parameters. The addition of 5% milkfish bone flour was proven to enhance the nutritional content of white bread without reducing consumer acceptance, while also promoting the functional and economic utilization of fishery waste.